AB0770 Serum Calcidiol, Dual-Energy X-Ray Absorptiometry and Lung Respiratory Tests in Patients with Interstitial Lung Diseases. (15th July 2016) - Pieren, A.; Tornero, C.
Abstract : Background: Vitamin D plays an essential paper in the regulation of the bone metabolism. Its role in the modulation of the autoimmune system is better known every day as well as its involvement in the pathogenesis of the autoimmune diseases. Some studies have shown a possible implication of the vitamin D in the development of lung diseases, as the interstitial lung diseases (ILD) through the inhibition of the fibroblasts' profibrotic phenotype. Likewise, it's been described a possible association between serum calcidiol levels and a decreased pulmonary function. Objectives: Analyze the prevalence of vitamin D insufficiency. Evaluate a possible relationship between calcidiol levels and lung respiratory tests. Asses the prevalence of low bone mineral density (BMD) and its correlation with risk factors. Methods: Retrospective study of a cohort of patients with ILD referred from the pulmonary consultation. We analyzed demographic and analytics aspects, dual-energy x-ray absorptiometry (DXA), spinal column radiographies, and lung respiratory tests. The statistical study was performed with SPSS. Results: 44 patients were recruited, 68% women with median age 66 years. 45.5% presented an idiopathic ILD (Usual Interstitial Pneumonia (UIP), Nonspecific IP and Cryptogenic Organizing Pneumonia) and 40.1% sarcoidosis. The 20% left was composed by patients with ANCA-Vasculitis (2), Extrinsic Allergic Alveolitis (6) and ILD related to connective tissue diseases (3 Rheumatoid Arthritis). 79.5% had received corticosteroids with a median dose of 5 grams. The prevalence of vitamin D insufficiency (<30ng/dl) was 81.3%, 42.9% presented calcidiol levels under 20 ng/dl and 6.80% <10ng/dl. The creatinine clearance rate, age and ESR were correlated with calcidiol levels. Upon the studied factors, we found no statistically association between vitamin D levels and lung respiratory tests and neither with the DLCO. By contrast, we did find an indirect association between FVC and trochanteric BMD which was removed by adjustment for sex, age and smoking status. About the bone density measures, 33.3% presented a normal BMD, 47.6% osteopenia and 19% osteoporosis. BMD was related to the renal function in total hip, wards triangle, trochanter and intertrochanteric region. We established an inverse association between BMD and ESR too. In the subgroup analysis, we found a younger population in the sarcoidosis group with a greater BMD in total hip, trochanter and intertrochanteric region as well as a smaller FRAX index. There were no statistically significant differences in the prevalence of osteoporosis or osteopenia and the subtype of pneumopathy, middle levels of calcidiol and the other bone metabolism parameters. Conclusions: In our patients with ILD, we found a high prevalence of vitamin D insufficiency. Nonetheless, there was no association between calcidiol levels and a worse obstructive pattern as it has been described in other chronic lung diseases. It is especially interesting the indirect correlation established between BMD and ESR, concluding the own disease activity can play a determinant role in the regulation of the bone metabolism. Disclosure of Interest: None declared